2011
DOI: 10.1002/gcc.20910
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a novel MALT lymphoma cell line, ma‐1, from a patient with t(14;18)(q32;q21)‐positive Helicobacter Pylori‐Independent Gastric MALT Lymphoma

Abstract: Although t(11;18)(q21;q21), t(1;14)(p22;q32), and a few other genetic mutations are specific markers for the Helicobacter pylori (HP)-independent status of gastric mucosa-associated lymphoid tissue (MALT) lymphoma, the molecular mechanisms responsible for HP-independence of gastric MALT lymphoma without such translocations and mutations remain uncharacterized. In the present study, we describe the establishment and characterization of a novel MALT lymphoma cell line, MA-1, which was derived from a gastric MALT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
19
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 53 publications
2
19
1
Order By: Relevance
“…Indeed, the possibility of follicular lymphoma in the present case was excluded by extensive histological and immunohistochemical studies: (1) the histological pattern of the lymphoma cells from the neck lymph node (small lymphoid cells mainly distributed in marginal zone) and Waldeyer's ring (centrocyte-like cells and prominent lymphoepithelial lesions) was identical to the lymphoma originally found in the stomach; (2) lack of the follicular-cell lymphoma-specific germinal cell markers CD10 or BCL6 in all clinical samples and MA-1 cells. Although the authors disagree with our findings that t(14;18)(q32;q21)/IGH-MALT1 and t(14;18)(q32;q21)/IGH-BCL2 coexist in MA-1 cells (Kuo et al, 2011), karyotypic analysis of the MA-1 cell line via G-banding and SKY showed multiple structural abnormalities with at least 13 alterations identified. Thus, the better description of the karyotype of translocation of MA-1 is ''der(14)t(14;18) (q32;q21).''…”
contrasting
confidence: 72%
See 4 more Smart Citations
“…Indeed, the possibility of follicular lymphoma in the present case was excluded by extensive histological and immunohistochemical studies: (1) the histological pattern of the lymphoma cells from the neck lymph node (small lymphoid cells mainly distributed in marginal zone) and Waldeyer's ring (centrocyte-like cells and prominent lymphoepithelial lesions) was identical to the lymphoma originally found in the stomach; (2) lack of the follicular-cell lymphoma-specific germinal cell markers CD10 or BCL6 in all clinical samples and MA-1 cells. Although the authors disagree with our findings that t(14;18)(q32;q21)/IGH-MALT1 and t(14;18)(q32;q21)/IGH-BCL2 coexist in MA-1 cells (Kuo et al, 2011), karyotypic analysis of the MA-1 cell line via G-banding and SKY showed multiple structural abnormalities with at least 13 alterations identified. Thus, the better description of the karyotype of translocation of MA-1 is ''der(14)t(14;18) (q32;q21).''…”
contrasting
confidence: 72%
“…In their correspondence, Flossbach et al have performed cytogenetic investigations (G-banding, CGH, FISH, and M-FISH) on the MALT-lymphoma cell line, MA-1, developed by Kuo et al (2011). The authors demonstrated largely the same karyotypic findings as published by Kuo et al (2011).…”
mentioning
confidence: 65%
See 3 more Smart Citations